A STACKED RECORD OF RELATIVE GEOMAGNETIC PALEOINTENSITY FOR THE PAST 270 KYR FROM THE WESTERN CONTINENTAL RISE OF THE ANTARCTIC PENINSULA - Macrì P.; Sagnotti L.; Lucchi R.G.; Rebesco M. (My University, 2006)
Paleomagnetic and rock magnetic investigations were carried out on four gravity cores recovered from the western continental rise of the Antarctic Peninsula during the SEDANO II cruise of RV OGS-Explora. The studied cores, each about 6.5 m-long, were collected at a depth of 3700-4100 m below the sea level, on the distal gentle side of sediment Drift 7, and consist of very fine-grained sediments spanning through various glacial-interglacial cycles. Detailed analysis of the paleomagnetic and rock magnetic data allowed to reconstruct relative paleointensity (RPI) records (NRM20 mT/ARM20 mT) for each core. We established a refined age model for the studied sequences by correlating individual SEDANO RPI curves to the global RPI stack SINT-800 [Y. Guyodo, J.-P. Valet, Global changes in intensity of the Earth's magnetic field during the past 800 kyr, Nature 399 (1999) 249-252]. The individual normalized SEDANO RPI records are in mutual close agreement; they were thus merged in a RPI stacking curve spanning the last 270 kyr and showing a low standard deviation. This study also points out that RPI records may provide a viable tool to date otherwise difficult-to-date sedimentary sequences, such as those deposited along peri-Antarctic margins. The new RPI chronology indicates that the sampled sedimentary sequence is younger than previously thought and allows a new high-resolution correlation to oxygen isotope stages. Furthermore, we recognized variations in the rock magnetic parameters that appear to be climatically-driven, with changes in the relative proportion of two magnetic mineral populations with distinct coercivities. Rock magnetic and lithological trends observed in the SEDANO cores indicate that during the climatic cycles of the Late Pleistocene this sector of the peri-Antarctic margin was subjected to subtle, yet identifiable, environmental changes, confirming a relatively higher instability of the West Antarctic ice sheet with respect to the East Antarctic counterpart. © 2006 Elsevier B.V. All rights reserved.
Keywords: ANTARCTICA; ENVIRONMENTAL MAGNETISM; GEOMAGNETIC RELATIVE PALEOINTENSITY; PALEOMAGNETISM; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Quaternary::Pleistocene